Optimal Investment Portfolio Analysis Using The Markowitz Model For Stock In Each Sector In The Indonesia Stock Market During Covid 19 (2020-2021) - Meliala, Fitria Ulina; Sukarno, Subiakto (Publikasi Indonesia, 2023)
The COVID 19 pandemic in early March 2020 starting from Wuhan had a very large impact on the global economy and the Indonesian economy, the COVID 19 pandemic forced the government to establish a PPKM policy (Implementation of Restrictions on Community Activities) to suppress the spread of Covid 19 in Indonesia. Indonesia's State Gross Domestic Product fell in the second quarter 2021 amounting to -5.32% and also having an impact on the stock market in Indonesia at January 02 2020 the JCI was recorded at 6283 fell to 3937 in March 24 2020 (minus 36.77%) in March 2020. The results of this study using 22 of the stocks representing 11 sectors in the stock market in Indonesia obtained a maximum Sharpe ratio calculation of 31.57% with a weekly yield of 1.48% and a standard deviation of 4.39% and a maximum yield with a Sharpe ratio of 31.29% and a yield weekly yield of 1.37% and a standard deviation of 4.08%, the result of the minimum standard deviation with a Sharpe ratio of 5.92% with a weekly yield of 0.24% and a standard deviation of 2.51% and the results of Portfolio in the efficient frontier namely portfolio 6 with a Sharpe ratio of 30.94% and weekly yield of 1.3% and a standard deviation of 3.9%. For investors who want to optimize their portfolio, they can choose stocks with optimal Sharpe ratios that already pay attention to risk-adjusted return.